Chemical Synthesis, Sintering and Piezoelectric Properties of Ba0.85Ca0.15 Zr0.1Ti0.9O3 Lead‐Free Ceramics. Issue 8 (8th May 2015) - Castkova, Klara; Maca, Karel; Cihlar, Jaroslav; Hughes, Hana; Matousek, Ales; Tofel, Pavel; Bai, Yang; Button, Tim W.; Ihlefeld, J.
<x xml:space="preserve">Abstract</x> The preparation of Ba0.85Ca0.15 Zr0.1Ti0.9O3 (BCZT) powders by wet chemical methods has been investigated, and the powders used to explore relationships between the microstructure and piezoelectric properties (d33 coefficient) of sintered BCZT ceramics. Sol–gel synthesis has been shown to be a successful method for the preparation of BCZT nanopowders with a pure tetragonal perovskite phase structure, specific surface area up to 21.8 m2/g and a mean particle size of 48 nm. These powders were suitable for the fabrication of dense BCZT ceramics with fine‐grain microstructures. The ceramics with the highest density of 95% theoretical density (TD) and grain size of 1.3 μm were prepared by uniaxial pressing followed by a two‐step sintering approach which contributed to the refinement of the BCTZ microstructure. A decrease in the grain size to 0.8–0.9 μm was achieved when samples were prepared using cold isostatic pressing. Using various sintering schedules, BCZT ceramics with broad range of grain sizes (0.8–60.5 μm) were prepared. The highest d33 = 410.8 ± 13.2 pC/N was exhibited by ceramics prepared from sol–gel powder sintered at 1425°C, with the relative density of 89.6%TD and grain size of 36 μm.